Synthetic N-acetyl-D-glucosamine based fully branched tetrasaccharide, a mimetic of the endogenous ligand for CD69, activates CD69+ killer lymphocytes upon dimerization via a hydrophilic flexible linker - Kovalová, Anna; Ledvina, Miroslav; Saman, David; Zyka, Daniel; Kubícková, Monika; Zídek, Lukás; Sklenár, Vladimír; Pompach, Petr; Kavan, Daniel; Bílý, Jan; Vanek, Ondrej; Kubínková, Zuzana; et al. (Journal of medicinal chemistry, 2010)
On the basis of the highly branched ovomucoid-type undecasaccharide that had been shown previously to be an endogenous ligand for CD69 leukocyte receptor, a systematic investigation of smaller oligosaccharide mimetics was performed based on linear and branched N-acetyl-d-hexosamine homooligomers prepared synthetically using hitherto unexplored reaction schemes. The systematic structure-activity studies revealed the tetrasaccharide GlcNAcbeta1-3(GlcNAcbeta1-4)(GlcNAcbeta1-6)GlcNAc (compound 52) and its alpha-benzyl derivative 49 as the best ligand for CD69 with IC(50) as high as 10(-9) M. This compound thus approaches the affinity of the classical high-affinity neoglycoprotein ligand GlcNAc(23)BSA. Compound 68, GlcNAc tetrasaccharide 52 dimerized through a hydrophilic flexible linker, turned out to be effective in activating CD69(+) lymphocytes. It also proved efficient in enhancing natural killing in vitro, decreasing the growth of tumors in vivo, and activating the CD69(+) tumor infiltrating lymphocytes examined ex vivo. This compound is thus a candidate for carbohydrate-based immunomodulators with promising antitumor potential.
Keywords: molekulární mimikry; Antigens, CD; lektiny typu C; Ligands; Models, Molecular; Oligosaccharides; CD antigeny; Acetylglucosamine; techniky in vitro; Drug Screening Assays, Antitumor; Humans; ligandy; Molecular Sequence Data; dimerizace; molekulární sekvence - údaje; Female; Antineoplastic Agents; krysa rodu Rattus; Dimerization; Lectins, C-Type; lidé; Recombinant Proteins; zvířata; myši; molekulární modely; Lymphocyte Activation; myši inbrední C57BL; buňky NK; Mice; Killer Cells, Natural; acetylglukosamin; NK Cell Lectin-Like Receptor Subfamily B; rekombinantní proteiny; imunologické faktory; aktivace lymfocytů; ženské pohlaví; diferenciační antigeny T-lymfocytů; Mice, Inbred C57BL; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; oligosacharidy; Antigens, Differentiation, T-Lymphocyte; Carbohydrate Sequence; Immunologic Factors; In Vitro Techniques; Rats; sacharidové sekvence; lektinové receptory NK-buněk - podrodina B; Animals; Cell Line, Tumor; Melanoma, Experimental; melanom experimentální; Molecular Mimicry